2013
DOI: 10.1108/jhtt-01-2013-0001
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of user‐generated content for hotel experiences

Abstract: Purpose -The broad goal of the study is to determine how travelers communicate in the cyberspace in relation to their positive and negative experiences they had when staying in a particular hotel. Further goals of this study include identifying the main themes that motivate consumers to evaluate hotel experiences in online environments and categorize the most frequently mentioned areas in the online hotel reviews. Design/methodology/approach -Content analysis techniques were applied by using the software tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(133 citation statements)
references
References 49 publications
3
120
0
10
Order By: Relevance
“…É de salientar também o facto de os consumidores recorrerem a informação gerada por outros acerca dos produtos antes de procederem a uma compra, principalmente se esta for de elevado envolvimento (Cheong & Morrison, 2008). Estas alterações ocorreram também no setor do turismo, em que os próprios consumidores utilizam informações do meio online, como reviews sobre viagens ou hotéis, ou passa-a-palavra para tomarem as suas decisões (Ye, Law, Gu & Chen, 2011), tendo estas informações um grande impacto nas suas perceções da marca (Barreda & Bilgihan, 2013).…”
Section: A Consumer Journeyunclassified
“…É de salientar também o facto de os consumidores recorrerem a informação gerada por outros acerca dos produtos antes de procederem a uma compra, principalmente se esta for de elevado envolvimento (Cheong & Morrison, 2008). Estas alterações ocorreram também no setor do turismo, em que os próprios consumidores utilizam informações do meio online, como reviews sobre viagens ou hotéis, ou passa-a-palavra para tomarem as suas decisões (Ye, Law, Gu & Chen, 2011), tendo estas informações um grande impacto nas suas perceções da marca (Barreda & Bilgihan, 2013).…”
Section: A Consumer Journeyunclassified
“…Oh, Fiore, and Jeong (2007) conducted a survey and identified that the aesthetic dimension of an experience for hotel guests is the most dominant factor in producing arousal, memory, overall equity, and satisfaction. Barreda and Bilgihan (2013) assayed a similar issue in the context of online hotel reviews. The results revealed that cleanliness and human contact were essential determinants of hotel experience satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Stringam and Gerdes Jr (2010) examined the link between textual data and the corresponding ratings which travelers assigned to the hotels. Additionally, Barreda and Bilgihan (2013) utilized the text mining method on TripAdvisor posts to determine factors that may affect brand image. The present study applies an approach which has been adopted by a number of more recent studies in order to acquire a targeted set of textual data.…”
mentioning
confidence: 99%